France and Algerian conscription in colonial times: Roots and consequences - Rehai MOHAMED & Riad BOUDELAA (Akofena)
Abstract: The French colonialists enacted numerous oppressive legislations against the Algerian people, aiming to solidify and expand the foundations of occupation throughout Algerian territory. Among these legislations was the conscription law, which sought to exploit Algerian youth to reinforce the combat fronts within the French army both internationally and locally. This article aims to shed light on the roots of the conscription issue in Algeria before 1912, as well as the circumstances surrounding the enactment of the conscription law and its content, and then the Algerians' stance on it.